Caribbean literature and the public sphere : from the plantation to the postcolonial - Dalleo, Raphael (New World studies., 2011)
"Bringing together the most exciting recent archival work in anglophone, francophone, and hispanophone Caribbean studies, Raphael Dalleo constructs a new literary history of the region that is both comprehensive and innovative. He examines how changes in political, economic, and social structures have produced different sets of possibilities for writers to imagine their relationship to the institutions of the public sphere. In the process, he provides a new context for rereading such major writers as Mary Seacole, Jose Marti, Jacques Roumain, Claude McKay, Marie Chauvet, and George Lamming while also drawing lesser-known figures into the story. Dalleo's comparative approach will be important to Caribbeanists from all the region's linguistic traditions, and his book contributes even more broadly to debates in Latin American and postcolonial studies about postmodernity and globalization."--Back cover